2014
DOI: 10.1024/1662-9647/a000113
|View full text |Cite
|
Sign up to set email alerts
|

Can the Mini-Mental State Examination Predict Capacity to Consent to Treatment?

Abstract: This study examines the relationship between capacity to consent to treatment as measured by the MacArthur Competence Assessment Tool for Treatment (MacCAT-T) and severity of cognitive impairment as measured with the Mini-Mental State Examination (MMSE). It also looks at the role of verbal retrieval in this relationship. We hypothesized that the often-quoted correlation between the MacCAT-T and the MMSE lies mainly in the joint dependence on verbal retrieval ability. Potential subjects were recruited from memo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria. Investigators in 29 studies discussed consent in patients with only medical conditions, 29 in patients with cognitive impairments only, and 19 in patients with both medical and cognitive issues or frail or vulnerable elderly (eTable 1, available online at the end of this article).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…1315,17,21,22,2426,28,29,31,32,34–36,3841,4345,4863,66,69,70,74,7680,8284,8690,92 The studies reviewed were from a variety of international settings: United States (n = 33); United Kingdom (n = 7); France (n = 5); the Netherlands (n = 5); Spain (n = 3); and Canada, Sweden, Finland, Germany, Switzerland, Turkey, Hong Kong, Scotland, Norway, Italy, South Africa, Israel, Korea, Austria, and Nigeria. Investigators in 29 studies discussed consent in patients with only medical conditions, 29 in patients with cognitive impairments only, and 19 in patients with both medical and cognitive issues or frail or vulnerable elderly (eTable 1, available online at the end of this article).…”
Section: Resultsmentioning
confidence: 99%
“…Investigators in 3 studies mentioned use of the MacCAT for Clinical Research understanding scale. 38,62,66 Information provided to patients, physician’s communication with patients, role of medical staff, and patient companions are some of the factors that affect patient understanding. 21,22,35 Investigators in 5 studies suggested educational intervention or computer-based tutorials to improve patient understanding.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations